Idea colliders the future of science museums - Gorman, Michael John 1971- (The MIT Press, 2020)
"An exploration of where the science museum is headed in the 21st century--from the traditional curiosity exposition of 19th century to contemporary hybrid/interactive models"--
Keywords: Prognose; Naturwissenschaftliches Museum; Zukunft; Science museums